Form Pressure in Composite Columns of 3DPC and SCC - Silfwerbrand Johan (Nordic Concrete Research)
Self-compacting concrete (SCC) and 3D printed concrete (3DPC) are two exciting technologies with potential to increase both the productivity and the working environment in the concrete industry. Permanent 3DPC formwork filled with SCC constitutes an interesting alternative for columns. The goal is to create a composite column with complete bond between the form and the core. Laboratory studies on composite columns of this type have been conducted at KTH investigating form pressure, load-carrying capacity, and durability. This paper is focusing on the form pressure that has been an issue ever since SCC was developed in Japan in the early 1990s because of the flowing nature of this concrete type. Two tests series have been performed. In the first one, two 2.4 m high composite columns with radius R = 0.25 m were tested. The casting rate was 2.6 m/h and resulted in a form pressure approaching full hydrostatic pressure but no form failures or any leakage arose. In the second test series, four composite columns with height h = 3.0 m and R = 0.15 m were cast at a casting rate r = 1 m/h. The form pressure was close to the one calculated with Gardner’s model. No failures, cracks or leakage occurred. The results are promising but tests on columns with larger dimensions would be of even larger interest.